Transport chains in the time of the Egyptian Pharaohs: a still unknown organizational efficiency - Paché, Gilles (Technium Social Sciences Journal, 2023)
The Egypt of the Pharaohs has been the subject of a huge deal of research by historians, archaeologists, and engineering specialists over the past decades. The construction of immense pyramids is largely the focus of attention insofar as it bears witness to the human genius capable of erecting monuments that have survived the millennia. The question of the logistics management involved in these majestic constructions is still little known, or at least rarely addressed. It is however undeniable that without a perfect organization of transport chains, the construction of the pyramids could not have been achieved. This article uses the example of the Great Pyramid of Giza to illustrate this point, the importance of which must be recognized by researchers specializing in management science.